PENGARUH MARKETING MIX TERHADAP KEPUTUSAN PEMBELIAN PERUMAHAN DI BANTUL: (STUDI PADA PERUMAHAN PONDOK PERMAI GIWANGAN) - Ariska Diyaastuty; Dila Damayanti (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2021)
This study is aimed to analyze the effect of product, price, place and promotion of the decision of buying a house in the Residence of Pondok Permai Giwangan. This research is a quantitative research that use interview and survey method. The data collection method is done by filling out questionnaires with 45 people respondent. The data analysis techniques of the research use validity test, reliability test, multiple regression analysis, partial test (t test), and simultaneous test (f test) using SPSS 22.0 software. The result of the data in t test indicate that product is the most dominant variable with t value count 4,722 greather than t table 2,021 and f test count equal to 27,992 greather than f table 2,60 with significance value 0,000 less than 0,05, thus, Ho is rejected and Ha is accepted because the significance value of F test is indicated less than 5%. Therefore, it can be concluded that all independent variables in this study simultaneously affect the decision of buying a house in the residence of Pondok Permai Giwangan.